Marketing Public Relations for Hospital Brand Awareness through Indonesian Cultural Communication - Renata Anisa; Hanny Hafiar; Retasari Dewi; Yustikasari Yustikasari; Nguyen Tan Khang (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
Marketing public relations (MPR) combines marketing and PR to build connections with stakeholders, brand awareness, the company's reputation, and consumer loyalty. Indonesia's healthcare business is rapidly changing, increasing hospital competitiveness. Indonesian healthcare, it involves disseminating information and promoting cultural characteristics including collectivism, empathy, and community-oriented communication. Rumah Sakit Universitas Indonesia (RSUI) functions as an academic medical center that integrates education, research, community service, and public health services, all grounded in a patient-centered approach. However, public awareness of its public health services remains suboptimal. This study aimed to explore MPR strategies implemented by RSUI in building brand awareness. A qualitative case study was conducted using literature analysis, observation, and in-depth interviews with hospital marketing. RSUI uses push, pull, and pass MPR strategies. The push strategy offers discounted prices to University of Indonesia faculty. Through partnerships, promotions, educational programs, and special events, the pull strategy engages consumers, patients, and the community. The pass strategy includes community and health center-focused corporate social responsibility, health education, and sports. Conclusion: RSUI uses MPR to raise brand exposure on websites, Facebook, X, Instagram, and YouTube to reach diverse stakeholders. Local communication culture values interpersonal warmth, mutual trust, and community participation to promote hospital credibility and public awareness.Keywords: Public relations, marketing public relations, hospital, brand awareness, digital mediaÂ ABSTRAKPemasaran Hubungan Masyarakat menggabungkan pemasaran dan hubungan masyarakat untuk membangun hubungan dengan pemangku kepentingan, kesadaran merek, reputasi perusahaan, dan loyalitas konsumen. Pemasaran hubungan masyarakat di bidang kesehatan di Indonesia melibatkan penyebaran informasi dan promosi karakteristik budaya, termasuk kolektivisme, empati, dan komunikasi yang berorientasi pada komunitas. Bisnis kesehatan di Indonesia mengalami perubahan yang cepat, meningkatkan persaingan antar rumah sakit. Rumah Sakit Universitas Indonesia (RSUI) memberikanÂ layanan pendidikan, penelitian, dan pelayanan publik. Masyarakat belum memahami fungsi rumah sakit universitas. Penelitian ini bertujuan mengeksplorasi secara mendalam implementasi strategi marketing public relations di rumah sakit universitas untuk membangun eksposur merek. Metode yang digunakan adalah studi kasus kualitatif dengan analisis literatur, observasi, dan wawancara dengan tim pemasaran rumah sakit. Hasil penelitian menunjukkan bahwa RSUI menggunakan strategi pemasaran humas push, pull, dan pass. Strategi push menawarkan potongan harga kepada komunitas. Melalui kemitraan, promosi, program pendidikan, dan special event, strategi pull melibatkan konsumen, pasien, dan masyarakat. Strategi pass mencakup tanggung jawab sosial perusahaan yang berfokus pada masyarakat dan pusat kesehatan, pendidikan kesehatan, dan olahraga. Kesimpulan: RS menggunakan pemasaran hubungan masyarakat untuk meningkatkan eksposur merek di situs web, Facebook, X, Instagram, dan YouTube, dengan menyesuaikan strategi untuk berbagai pemangku kepentingan. Budaya komunikasi lokal mengutamakan kehangatan antarindividu, kepercayaan mutual, dan partisipasi komunitas untuk meningkatkan kredibilitas rumah sakit dan kesadaran publik.Â Kata Kunci: Hubungan masyarakat, pemasaran hubungan masyarakat, rumah sakit, kesadaran merek, media digital